Poly(acrylic acid)-poly(ethylene glycol) layers on positively charged surface coatings: molecular structure, protein resistance, and application to single protein deposition - Seehuber, Andrea; Schmidt, Dennis; Dahint, Reiner (Langmuir, 2012)
A new copolymer (PAA-PEG2000) has been designed, consisting of a negatively charged poly(acrylic acid) (PAA) backbone to which poly(ethylene glycol) (PEG) side chains with a molecular weight of about 2 kDa were grafted in a molecular ratio of 3:10. It readily adsorbs to positively charged surfaces and may be considered to be the anionic counterpart of PEG-grafted poly(l-lysine) (PLL-PEG), which was first described by Kenausis et al. and is widely used to render negatively charged surfaces protein-resistant. The synthesis of PAA-PEG2000 can be carried out in aqueous solution at room temperature and does not require any sophisticated techniques such as handling in an inert gas atmosphere. Using ellipsometry and infrared reflection absorption spectroscopy (IRRAS), the film structure has been carefully analyzed for copolymer adsorption onto three different positively charged surfaces, namely, thin layers of poly(allylamine) (PAH), poly(ethyleneimine) (PEI) and (3-aminopropyl)triethoxysilane (APTES). Besides the film thickness, the conformation of the PEG chains and their orientation with respect to the surface normal appear to be important parameters for the protein resistance of the films. Although PAA-PEG2000 adsorbed to PAH and PEI renders the surfaces inert, only partial protein resistance has been observed if the copolymer is deposited on APTES. In a model application, we have generated heterogeneous surfaces composed of isolated small Au nanoparticles (AuNP's) embedded in a protein-resistant layer of PAA-PEG2000 and demonstrated that the AuNP's can serve as adsorption sites for single protein species. In the future, these nanopatterned surfaces may be used for the investigation of isolated proteins.
Published: May 9, 2012
Gesehen am 27.06.2018